Using an experiment among clinical experts to determine the cost and clinical impact of rapid whole exome sequencing in acute pediatric settings - Kapol, Nattiya; Kamolvisit, Wuttichart; Kongkiattikul, Lalida; Huang-Ku, Evan; Sribundit, Namfon; Lochid-Amnuay, Surasit; Samprasit, Nathapol; Dulsamphan, Thamonwan; Juntama, Parntip; Suwanpanich, Chotika; Boonsimma, Ponghathai; Shotelersuk, Vorasuk; et al. (Frontiers in Pediatrics, 2023)
Objective: Evaluate the cost and clinical impacts of rapid whole exome sequencing (rWES) for managing pediatric patients with unknown etiologies of critical illnesses through an expert elicitation experiment. Method: Physicians in the intervention group (n=10) could order rWES to complete three real-world case studies, while physicians in the control group (n=8) could not. Costs and health outcomes between and within groups were compared. Results: The cost incurred in the intervention group was consistently higher than the control by 60,000 to 70,000 TBH. Fewer other investigation costs were incurred when rWES could provide a diagnosis. Less cost was incurred when an rWES that could lead to a change in management was ordered earlier. Diagnostic accuracy and the quality of non-pharmaceutical interventions were superior when rWES was available. Conclusion: In acute pediatric settings, rWES offered clinical benefits at the average cost of 60,000 to 70,000 TBH. Whether this test is cost-effective warrants further investigations. Several challenges, including cost and ethical concerns for assessing high-cost technology for rare diseases in resource-limited settings, were potentially overcome by our study design using expert elicitation methods.